2018
DOI: 10.1021/acs.jpcc.8b00257
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Electronic and Optical Properties of Monolayer and Multilayer Janus MoSSe as a Photocatalyst for Solar Water Splitting: A First-Principles Study

Abstract: Recently, novel two-dimensional materials for solar water splitting have drawn enormous research attention for the interesting tunable electronic and optical properties. We investigate the geometry, electronic, and optical properties of the monolayer (ML) and multilayer Janus MoSSe with the first-principles calculations. We find that the ML Janus MoSSe is a semiconductor with a direct band gap of 2.14 eV, which is suitable for absorbing visual light efficiently. It also holds an appropriate band edge alignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
175
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(187 citation statements)
references
References 71 publications
10
175
1
1
Order By: Relevance
“…Similar to the traditional MX 2 , the bandgap of MoSSe increases with a decrease in thickness due to the quantum confinement effect. [55] For the N 2 XY (NN′X 2 ) monolayers, the Ga 2 STe, Ga 2 SeTe, In 2 Ste, and In 2 SeTe are direct bandgap semiconductors, with the CBM and VBM located at the Γ point, while the Ga 2 SSe, In 2 SSe, GaInS 2 , GaInSe 2 , and GaInTe 2 are indirect bandgap semiconductors. The bandgap of Janus N 2 XY (NN′X 2 ) ranges from 0.89 to 2.03 eV, which is slightly smaller than the conventional NX monolayers.…”
Section: Band Structurementioning
confidence: 99%
“…Similar to the traditional MX 2 , the bandgap of MoSSe increases with a decrease in thickness due to the quantum confinement effect. [55] For the N 2 XY (NN′X 2 ) monolayers, the Ga 2 STe, Ga 2 SeTe, In 2 Ste, and In 2 SeTe are direct bandgap semiconductors, with the CBM and VBM located at the Γ point, while the Ga 2 SSe, In 2 SSe, GaInS 2 , GaInSe 2 , and GaInTe 2 are indirect bandgap semiconductors. The bandgap of Janus N 2 XY (NN′X 2 ) ranges from 0.89 to 2.03 eV, which is slightly smaller than the conventional NX monolayers.…”
Section: Band Structurementioning
confidence: 99%
“…[14] The Janus MoSSe monolayer is a direct semiconductor with a band gap of 1.35 eV. [16][17][18] Guan et al [19] demonstrated that Janus MoSSe is a potential candidate for photocatalytic water splitting with enhanced activity originating from the asymmetrical structure. Jin et al [20] found that Janus MoSSe is an ideal material for nanoscale sensors with high gas sensitivity and surface selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since the electronic properties of nanomaterials can be well adjusted by external stimuli, it has been found that tensile strain and transition metal atom adsorption could strengthen optical absorption [9,29]. More interestingly, in 2D Janus MoSSe BL, the light absorption can be improved effectively by changing the stacking configurations [10,11,15].…”
Section: Utilization Of Sunlightmentioning
confidence: 99%
“…This will substantially enhance the light utilization efficiency. Motivated by these beneficial properties, a large number of 2D Janus single layers (SLs) and bilayers (BLs) have been designed for the application of photocatalytic water splitting, such as III 2 XY (III = Ga and In; X, Y = S, Se, and Te, and X ̸ = Y) SLs [7,8], MXY (M = Mo, W) SL and BL [9][10][11][12][13], ScXY SLs [14], PtSSe SL and BL [15], and MXZ (M = Zr, and Hf; X = S and Se; Z = O and S; X ̸ = Z) SLs [16]. Based on the reaction mechanism, photocatalytic water splitting can be divided into four steps (see figure 1(b)): (1) adsorption of water molecules, (2) utilization of sunlight, (3) charge separation and transport, and (4) surface hydrogen evolution reaction (HER) and oxygen evolution reaction (OER).…”
Section: Introductionmentioning
confidence: 99%